Central Locker System for shopping mall using NFC Based Smartphone - Poddar, Siddarth (Discoveries in Agriculture and Food Sciences, 2014)
Depositing purchased item at each store’s locker system and carrying a token in hand for the assigned locker while entering a store in a shopping mall as well as collecting the item back while exiting the store is a time consuming exercise and even long delayed if the token is lost. The time would even multiply visiting multiple numbers of stores in a mall. Sometimes waiting in a long queue for depositing item at the store is an irritating hassle and everyone wants to skip this hassle. This paper introduces a novel solution using NFC enabled Smartphone and NFC reader located at each checkout counter of the store which provides an easy and convenient way to immediately keep your purchased things safe at the centrally located locker system and move around openly. Locker number would be generated at the store checkout counter after purchasing the item and just a tap of smartphone on NFC reader save the locker number information on NFC application installed on smartphone, which is used to retrieve the item back while exiting the mall. With the proposed solution, usage of extra space for each store’s locker system and the corresponding staff can be eliminated, leading to cost reduction, promote efficiency and enhance customer service experience.